THE ROLE OF HYPERHOMOCYSTEINEMIA IN THE DEVELOPMENT OF COGNITIVE IMPAIRMENT IN CHRONIC CEREBRAL ISCHEMIA - Xatamova Sarvinoz Muyitdinovna (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Summary Increased levels of C-reactive protein (CRP) and hypercomocysteinemia are considered as independent factors for the development of endothelial damage and atherosclerosis. The sluggish inflammatory process that occurs in the endothelium is usually not associated with infections. The accumulation of homocysteine leads to loosening of the walls of the arteries, the appearance of local defects in the endothelium. People with high homocysteine levels in this group have an increased risk of Alzheimer’s disease and cognitive impairment.